2020
DOI: 10.1371/journal.pone.0232927
|View full text |Cite
|
Sign up to set email alerts
|

Substantial improvement of tetraene macrolide production in Streptomyces diastatochromogenes by cumulative drug resistance mutations

Abstract: Tetraene macrolides remain one of the most reliable fungicidal agents as resistance of fungal pathogens to these antibiotics is relatively rare. The modes of action and biosynthesis of polyene macrolides had been the focus of research over the past few years. However, few studies have been carried out on the overproduction of polyene macrolides. In the present study, cumulative drug-resistance mutation was used to obtain a quintuple mutant G5-59 with huge tetraene macrolide overproduction from the starting str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Toyocamycin is a nucleoside antibiotic and generated by the fermentation of Streptomyces diastatochromogenes 1,628. It exhibits both antibacterial and antifungal activities and effective against pathogenic fungi, including Rhizoctonia solani and Fusarium oxysporum ( Fan et al, 2020 ). Tebuconazole is a broad-spectrum triazole fungicide and causes DNA damage and induces the mitochondrial apoptotic pathway in the fungal pathogens of plants ( Muñoz-Leoz et al, 2011 ), which could affect the fungus in the fat body.…”
Section: Introductionmentioning
confidence: 99%
“…Toyocamycin is a nucleoside antibiotic and generated by the fermentation of Streptomyces diastatochromogenes 1,628. It exhibits both antibacterial and antifungal activities and effective against pathogenic fungi, including Rhizoctonia solani and Fusarium oxysporum ( Fan et al, 2020 ). Tebuconazole is a broad-spectrum triazole fungicide and causes DNA damage and induces the mitochondrial apoptotic pathway in the fungal pathogens of plants ( Muñoz-Leoz et al, 2011 ), which could affect the fungus in the fat body.…”
Section: Introductionmentioning
confidence: 99%
“…5C ). Similarly, the transcriptional level of genes tetC and tetK ( 18 ) in tetraene macrolide cluster downregulated, while the expression of negatively transcriptional regulator tetR upregulated in the ppGpp 0 mutant by 2.29-fold at the late exponential phase, which was coherent with lower tetramycin P production ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 76%
“…Streptomyces produce various types of important bioactive metabolites, and many secondary metabolites were employed clinically as antibiotics. The two categories of secondary metabolites produced by S. diastatochromogenes 1628 have been identified as toyocamycin and tetramycin P, which was synthesized by the toy cluster (toyocamycin) ( 17 ) and the tetraene macrolide cluster (tetramycin P) ( 18 ). Previous studies showed that the stringent response could positively regulate the synthesis of secondary metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces diastatochromogenes 1628 is an important Gram-positive bacterium that is used to produce several kinds of antibiotics, including toyocamycin, tetramycin A, tetramycin P, and tetrin B, which are widely used in the fields of medicine, agriculture, and food [1][2][3][4]. Among them, toyocamycin, an alkaline nucleoside antibiotic (Figure 1B), exhibits antibacterial and antifungal activities [5].…”
Section: Introductionmentioning
confidence: 99%